Pembangunan Aplikasi Alat Musik Tradisional Kendang Berbasis Android - Farhan Muhammad Basir; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research aims to produce an application that introducing a traditional musical instrument called “kendang” that can be run on smart device that has Android operating system. This application could be used for everyone who interested in learning more about traditional musical instrument “Kendang”. The development method that used in this research is Multimedia Development Life Cycle (MDLC) and a software that used in the development of application is Android Studio with Java programming language. The result of this research is an application that could be run on Android operation system to get information about the traditional musical instrument “kendang” such as the shape, sound, history, and more.